Association between nutritional risk index and outcomes for head and neck cancer patients receiving concurrent chemo‐radiotherapy. Issue 9 (20th June 2020) - Oh, Justin; Liu, Alvin; Tran, Eric; Berthelet, Eric; Wu, Jonn; Olson, Robert A.; Chau, Nicole; Bowman, Angie; Hamilton, Sarah N.
Abstract: Background: Patients receiving chemoradiotherapy for head and neck cancer (HNC) are often malnourished. We assessed the utility of nutritional risk index (NRI) in HNC patients undergoing chemoradiotherapy. Methods: A population‐based retrospective review of HNC patients treated with curative chemoradiation was performed. Demographics, anthropometrics, overall survival (OS), and the composite treatment complication rate (G‐tube dependence, radiation incompletion, 90‐day mortality, and unplanned hospitalization) were collected. Results: Two hundred ninety‐two patients were identified. Average pretreatment and posttreatment NRI were 110 (SD 3) and 99 (SD 12), respectively ( P < .01). Pretreatment NRI risk category, age, ECOG status, and tumor subsites were associated with OS on multivariate analysis. Pretreatment NRI risk category was associated with risk of treatment related complications. Conclusions: There was a significant decrease between pretreatment and posttreatment NRI in HNC patients receiving chemoradiation. Pretreatment NRI risk category may predict OS and composite treatment complications. Investigation of NRI as a prognostic factor is warranted.